A STUDY OF TRADITIONAL & AGILE PROJECT MANAGEMENT AND THEIR APPLICATION IN A SME CONSTRUCTION COMPANY IN INDIA - Patel, Tanmay (2012)
This report has been compiled to shed light on methods employed under the Agile Project Management approach which, in recent times, has been given increasing importance and attention. It was observed that most of the literature regarding their application in the real world was limited to projects in large organizations. This research is based on this literature gap and aims to focus on projects in small organizations. This dissertation report is a primary research project based on studying the project management structure in a SME based in India. A literature review was carried out which related to the theoretical work of authors within the project management community. The researcher was thereby able to gain thorough understanding of the topic. Primary data was collected by interviewing the stakeholders in Shuvam Constructions Private Limited, a SME in the Indian Real-Estate construction industry. The data relating to project management practices in past projects was analyzed and it was found that the stakeholders lacked knowledge about Agile methods but some practices employed by them, in an informal manner, were in fact core values relating to those found in Agile methods. The report provided recommendations for improving the company’s project management structure and also pointed out the challenges it might face in applying these recommendations. Furthermore, this research aims to provide a contribution to the academic field in the country where it was conducted by setting a starting point for focused project management studies in India.